Clinical Implication of Vascular Cell Adhesion Molecule-1 and Very Late Activation Antigen-4 Interaction, and Matrix Metalloproteinase-2 Production in Patients with Liver Disease - Ikuko Haruta; Katsutoshi Tokushige; Tatsuji Komatsu; Ikuo Ikeda; Katsumi Yamauchi; Naoaki Hayashi (Canadian Journal of Gastroenterology)
OBJECTIVES: To clarify the role of adhesion molecule in liver cell injury.